Comparison of the Coracoid and Retroclavicular Approaches for Ultrasound-Guided Infraclavicular Brachial Plexus Block - Sunil Bablu Pulla; Mohd. Abdul Moiz (Academia Anesthesiologica International, 2020)
Background: The infrastructural brachial plexus block has a less possible risk of tourniquet pain during the surgery and a greater blocking of musculocutaneous and axillary nerves than the axillary block with one injection. If enough time is given for block start, the efficacy of the infra-clavicular brachial block can be increased. The objective is to Comparing the coracoid and retro clavicular approaches with an ultrasound brachial plexus block. Subjects and Methods : A total of One Hundred patients receiving IBPB block were randomly assigned into two groups, Coracoid-based group C and retro clavicular-based Group R. Results: Group R has greatly increased visibility of the needle tip compared with group C. Group R had a better view of the needle shaft than group C. In group R, block output time (2.8 1.48 minutes) was statistically lower than in group C (5.7 1.19 minutes). Anesthesia duration in group R (17.6 1.3) vs (21.2 2.0) was statistically shorter. The needle passes in group R were much less. Conclusion: The results of this study indicate that the ultrasound-guided ICB approach correlates with a higher needle tip and shaft vision, shorter periods of time and anesthesia, and with fewer needle passes than the coracoid approach. But in terms of success rates and patient satisfaction, the retro clavicular approach was identical to the coracoid technique.